Students’ Vocabulary Errors in Constructing Descriptive Text - Rostiana, Heva (Journal of English Education Studies, 2020)
This research is aimed to investigate an analysis on students’ vocabulary errors in constructing descriptive text at the First Grade Students of SMK IT Al-Halim. The research is conducted through content analysis. Data of the research are taken from documentation of description text and interview with the students of SMK IT Al-Halim. Result of the research shows that there were vocabulary error in constructing descriptive text; there were lexical error, syntactical error, and discourse error. The dominant of errors is in lexical error especially in spelling errors. Vocabulary error is caused they are lacks of awareness of students in increasing mastery of the vocabulary; English words have multiple meanings and confusion, so it makes them difficult in learning English. They are also bored and lazy to look for vocabulary. In other hand, the method used by the teacher does not appropriate in learning process. Therefore, the students should enrich vocabulary by memorize ten or more of vocabulary in one day. The students also should more often open dictionary. Furthermore, and the teacher should motivate the students in learning English. Then, the teachers should give clearly, explanation and clarification when teach English especially in vocabulary for students